The Association of Penile Fracture and Female Sexual Abnormalities - Baylan, Burhan; Kartal , İbrahim; Kokurcan, Alihan (Urology Journal, 2022)
Purpose: To study the effect of female sexual abnormalities on the etiology of penile fracture, which is an important urological emergency. Materials and Methods: The sexual function of the partners of patients with penile fracture (study group, n = 90) treated at our clinic and healthy women (control group, n = 90) were evaluated on a voluntary basis. In both groups, sexual function was evaluated with the Female Sexual Function Index (FSFI). Each substance of the FSFI was evaluated separately by comparing both groups and the effect on the development of penile fracture was investigated. Results: There was no difference in demographic and clinical characteristics between the study and control groups. Evaluation of sexual function with FSFI revealed that the scores of vaginal lubrication, orgasm, satisfaction, and pain subscales were lower in the study group (p < .001). Among these subscales, anorgasmia was determined as the factor with the largest effect on the development of penile fracture (OR = 7.333, 95% CI = 2.666–20.166, p < .001). No correlation was found between the largest dimension of penile fracture and FSFI total and subscale scores in the study group. Conclusion: We believe that female vaginal dryness and dyspareunia in particular are factors which could cause the development of penile fracture during sexual intercourse. The treatment could prevent the development of penile fracture in the male.